1993
DOI: 10.1159/000216915
|View full text |Cite
|
Sign up to set email alerts
|

Factor Xa Inhibition: Correlation between the Plasma Levels of Anti-Xa Activity and Occurrence of Thrombosis and Haemorrhage

Abstract: A multicentre, double-blind, randomised trial was conducted to compare the efficacy of a low-molecular-weight (LMW) heparin, Logiparin, with that of an unfractionated (UF) heparin in the prophylactic treatment of thrombosis in patients undergoing general surgery. A total of 1,290 patients were randomised to receive a single daily dose of Logiparin (2,500 IU: 431 patients; 3,500 IU: 430 patients) or UF heparin (2 × 5,000 IU: 429 patients). The incidence of the main end point, deep venous thrombosis, was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 13 publications
(18 reference statements)
1
37
0
1
Order By: Relevance
“…15 However, another study has shown that most major bleeds occurred in those patients receiving the highest doses of LMWH 16 and those with mean antiXa levels greater than 0.8 IU/mL. Other studies have shown that the pharmacokinetics of LMWH are altered during pregnancy.…”
Section: Resultsmentioning
confidence: 98%
“…15 However, another study has shown that most major bleeds occurred in those patients receiving the highest doses of LMWH 16 and those with mean antiXa levels greater than 0.8 IU/mL. Other studies have shown that the pharmacokinetics of LMWH are altered during pregnancy.…”
Section: Resultsmentioning
confidence: 98%
“…Levine et al [24] reported a highly significant association between anti-Xa levels and rates of venographically confirmed deep vein thrombosis and wound hematomas with LMWH prophylaxis following total hip arthroplasty. Other investigators have noted weaker associations between anti-Xa levels and deep vein thrombosis rates with LMWH prophylaxis following general surgery [19,22], but not for major orthopedic procedures [16,21,23,26].…”
Section: Discussionmentioning
confidence: 94%
“…In this context it needs to be born in mind that target ranges are different for different LMWHs, and that it is still unknown if targets derived from pharmacological studies in healthy volunteers are indeed applicable to the critically ill population with major, heterogeneous and unpredictable modifications in pharmacokinetics and pharmacodynamics, as well as changes in haemostatic competence. Another problem is the only weak relationship between anti-Xa activity and clinical occurrence of symptomatic and asymptomatic VTE [18][19][20]. However, determination of anti-Xa activity is recommended if renal elimination of LMWH is impaired [2].…”
Section: Discussionmentioning
confidence: 99%